Some Extensions of M-Fractions Related to Strong Stieltjes Distributions - Bracciali, Cleonice Fátima [UNESP]; McCabe, J. H. (Springer Nature, 2000)
The purpose of this paper is to show the symmetric relations that appear between the coefficients of some even and odd extensions of the M-fractions related to a certain kind of symmetric strong Stieltjes distribution.
Keywords: Continued fractions; Padé approximants; Symmetric distributions